Refuseapp: Waste Transportation Service Application - Jodi Setiawan (Universitas Pendidikan Indonesia (UPI), 2022)
Garbage is still a big problem throughout the world, including Indonesia. This waste problem has not yet found the right solution to deal with the increase in waste that continues to grow from year to year. Included in these problems are waste problems, both household waste and industrial or company waste. There are still wastes that cannot be processed and managed properly. The purpose of this study is to find solutions to minimize the accumulation of waste or waste, especially in the sector of an agency. The solution offered in this research is the design of an application called Refuseapp. This application functions as a waste transportation service devoted to the agency sector. This waste transportation service is provided free of charge in the hope of reducing the pile of waste that exists in the agency. The institutions in question are companies and hospitals. The waste to be transported will later be distributed to a waste processing site or waste bank and also to a final disposal site (TPA) in the area. The result of this research is the design of the Refuseapp application in the form of an application mockup.